The Impact of the Invest-and-Harvest Pricing Pattern on Lending and Policy Decisions Mortgage Market Regulation - Benardi Benardi; Hanifah Hanifah (LPPM STIE Kasih Bangsa, 2025)
This qualitative literature review investigates the impact of the 'invest-and-harvest' pricing pattern on mortgage lending decisions and market regulation policies. The analysis reveals that lenders often offer low-interest rates to attract new borrowers while charging higher rates to loyal renewers, influenced by search and switching frictions. These dynamics significantly affect market competition and have crucial policy implications. The study highlights the need for adaptive public policies that consider these pricing strategies to enhance market efficiency and fairness. Additionally, borrower heterogeneity plays a vital role, with lower-income and lower-credit-score borrowers benefiting more from long-term contracts. Despite its insights, the study is limited by its reliance on existing literature and its focus on developed markets, suggesting the need for further research in diverse contexts.